2015
DOI: 10.1016/j.msec.2014.10.072
|View full text |Cite
|
Sign up to set email alerts
|

Micro-poro-elasticity of baghdadite-based bone tissue engineering scaffolds: A unifying approach based on ultrasonics, nanoindentation, and homogenization theory

Abstract: Microstructure-elasticity relations for bone tissue engineering scaffolds are key to rational biomaterial design. As a contribution thereto, we here report comprehensive length measuring, weighing, and ultrasonic tests at 0.1MHz frequency, on porous baghdadite (Ca3ZrSi2O9) scaffolds. The resulting porosity-stiffness relations further confirm a formerly detected, micromechanically explained, general relationship for a great variety of different polycrystals, which also allows for estimating the zero-porosity ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Bone tissue engineering (BTE) aims at developing approaches and materials for a functional bone regeneration to restore, maintain or improve its physiological conditions. The most recent studies have identified in third generation scaffolds the suitable element for this purpose, where scaffold is intended as a template for cell attachment, in growth and differentiation as well as a construct favoring production, organization and maintenance of extracellular matrix . Yet, differences in scaffolding material, porosity, ability to mimic the organic and inorganic components of the extracellular matrix lead to different osteogenic differentiation and clinical outcomes .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone tissue engineering (BTE) aims at developing approaches and materials for a functional bone regeneration to restore, maintain or improve its physiological conditions. The most recent studies have identified in third generation scaffolds the suitable element for this purpose, where scaffold is intended as a template for cell attachment, in growth and differentiation as well as a construct favoring production, organization and maintenance of extracellular matrix . Yet, differences in scaffolding material, porosity, ability to mimic the organic and inorganic components of the extracellular matrix lead to different osteogenic differentiation and clinical outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…The most recent studies have identified in third generation scaffolds the suitable element for this purpose, where scaffold is intended as a template for cell attachment, in growth and differentiation as well as a construct favoring production, organization and maintenance of extracellular matrix. [1][2][3] Yet, differences in scaffolding material, porosity, ability to mimic the organic and inorganic components of the extracellular matrix lead to different osteogenic differentiation and clinical outcomes. [4][5][6] The requirements a scaffold must fulfill to achieve a successful result can be summarized in five points: composition, hierarchical organization, structure, customization, and load-bearing.…”
Section: Introductionmentioning
confidence: 99%
“…As a novelty, the authors resolved the mechanical behavior down to the subvoxel level, which is not shown any more by micro-CT but where one has to resort to electron microscopic techniques such as SEM in order to elucidate microfeatures such as the ones shown in Figure 1. These features explain the heterogeneous distributions of elastic and hardness properties at the single micron scale, 25,26 which are considered here by means of poro-micromechanics theory. 6 They are the source of load-induced heterogeneous stress distributions across the loaded objects, at both the polycrystalline level of the single FEs and the single crystal level within the FEs -that is, within the RVEs on which the porous biomaterial is defined.…”
Section: Discussionmentioning
confidence: 94%
“…Compression elastography has been demonstrated capable of visualizing differences in elastic properties of polymer samples with moduli ranging from 47 kPa to 4 MPa. 77 Other ultrasound techniques, have been employed to characterize the properties of porous baghdadite scaffolds 78 or bioglass-based scaffolds 79 used for bone tissue engineering. In these studies, pulse-echo ultrasound was used to measure the time-of-flight, estimate the longitudinal wave velocity, and then calculate the normal component of the stiffness tensor.…”
Section: Elastographymentioning
confidence: 99%
“…The normal component of the stiffness decreased monotonically with increasing biomaterial porosity. 78 However, this ultrasound technique does not provide quantitative measurement of the modulus of materials.…”
Section: Elastographymentioning
confidence: 99%